2018
DOI: 10.1016/j.scitotenv.2017.12.320
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cu impacts on freshwater diatoms: biochemical and metabolomic responses of Tabellaria flocculosa (Roth) Kützing

Abstract: Metals are a recognised threat to aquatic organisms but the impact of metals such as copper (Cu) on benthic freshwater diatoms is poorly understood, even if diatoms are commonly used as water quality indicators. Our study aimed to elucidate the cellular targets of Cu toxicity and the mechanisms cells resort to counteract toxicity and to increase tolerance to Cu. A concerted approach analysing the biochemical, physiological and metabolome alterations in diatom cells was conducted by exposing the freshwater diat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…These findings agree with previous results of (Gustavson et al, 1999), who also reported an increase of centric Bacillariophyta in marine phytoplankton as a consequence of Cu exposure. The Cu tolerance in diatoms has been linked with their capacity to synthetize extracellular polysaccharides and frustuline (Gonçalves et al, 2018). Nevertheless, previously published mesocsom studies also provide a partly conflicting picture of diatom tolerance to Cu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with previous results of (Gustavson et al, 1999), who also reported an increase of centric Bacillariophyta in marine phytoplankton as a consequence of Cu exposure. The Cu tolerance in diatoms has been linked with their capacity to synthetize extracellular polysaccharides and frustuline (Gonçalves et al, 2018). Nevertheless, previously published mesocsom studies also provide a partly conflicting picture of diatom tolerance to Cu.…”
Section: Discussionmentioning
confidence: 99%
“…Cu is an essential element (Festa and Thiele, 2011), but becomes toxic at higher concentrations (Amara et al, 2018), depending on metal speciation, accumulation (Meylan et al, 2004; Serra et al, 2009) and exposed organism (Barranguet et al, 2003; Amara et al, 2018). In photosynthetically active cells Cu inhibits CO 2 fixation and PSII activity (Pandey et al, 1992), causes oxidative stress and ultimately inhibits cell growth (Gonçalves et al, 2018). In bacteria, Cu affects various cellular enzymes and proteins involved in energy metabolism (Waldron et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…57 However, the present findings for IHg and MeHg are opposite to the decrease of some of the amino acids (lysine, arginine, and glutamine) observed in copper exposure of other green algae Chlorella sp., 58,59 Scenedesmus quadricauda, 60 and diatom Tabellaria flocculosa (Roth) Kuẗzing. 61 Nucleobase/-Tide/-Side Metabolism. The metabolism of both pyrimidine and purine derivatives was significantly affected in algae exposed to IHg and MeHg ( Figures S7 and S8).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, they produce extracellular polysaccharides (EPS) to immobilize metals outside the cells, such as copper. As a result, the excretion of these protective products reduces sensitivity to copper exposure [71][72][73]. So the more copper there is (up to a certain point whereat the concentration of metal is too high to be countered), the more EPS there are, and the more diatoms adhere strongly to the substratum.…”
Section: Marine Biofouling Field Testsmentioning
confidence: 99%